The Validity of Computed Tomography Guided Lung Tru- cut Biopsies in Achieving Accurate Tissue Results - Khashman, Basim Mohammed; Mohson, Khaleel I; Abdul Qader, Omar Abdul Jabbar; Abdul Ghafour, Kifah H. (Journal of Contemporary Medical Sciences, 2024)
Objective: This study aims to assess the efficacy of CT-guided true-cut biopsy as a less invasive and cost-effective diagnostic technique for peripherally placed lung lesions. Methods: fourty patients with solitary lung nodule were involved in this study, true cut biopsies under Ct guide was taken then processed for routine H&E staining. Results: different pathological features can be identified with different pathological features giving primary diagnostic screening for lung cancer Conclusion: CT guided thoracic lesion biopsy is very efficient, cost-effective and less invasive technique when compared with the thoracic surgery